Therapeutic potential of vasoactive intestinal peptide and its receptor VPAC2 in type 2 diabetes - Hou, Xintong; Yang, Dan; Yang, Guimei; Li, Mengnan; Zhang, Jian; Zhang, Jiaxin; Zhang, Yi; Liu, Yunfeng (Frontiers in Endocrinology, 2022)
Owing to the increasing prevalence of type 2 diabetes, the development of novel hypoglycemic drugs has become a research hotspot, with the ultimate goal of developing therapeutic drugs that stimulate glucose-induced insulin secretion without inducing hypoglycemia. Vasoactive intestinal peptide (VIP), a 28-amino-acid peptide, can stimulate glucose-dependent insulin secretion, particularly by binding to VPAC2 receptors. VIP also promotes islet β-cell proliferation through the forkhead box M1 pathway, but the specific molecular mechanism remains to be studied. The clinical application of VIP is limited because of its short half-life and wide distribution in the human body. Based on the binding properties of VIP and VPAC2 receptors, VPAC2-selective agonists have been developed to serve as novel hypoglycemic drugs. This review summarizes the physiological significance of VIP in glucose homeostasis and the potential therapeutic value of VPAC2-selective agonists in type 2 diabetes.